2010
DOI: 10.1159/000316656
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Mass Index and Migraine

Abstract: Objective: To explore the prevalence of overweight and obesity in patients with migraine. Background: Previous studies support the concept that obesity is an exacerbating factor for migraine. Also, some studies have found an increased frequency of obesity and overweight in migraine patients compared to the normal population. Methods: We studied 1,371 patients with migraine and 612 controls. The migraine population was matched by gender with a healthy control group. Results: Mean age of patients with migraine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
1
20
1
1
Order By: Relevance
“…These results are in line with our data in showing no significant difference in BMI groups and reduction of headache days with categorization of BMI into only two subgroups (< 25 vs. ≥ 25) and a longer follow-up (twelve months). High BMI was a risk factor for increasing headache frequency in some studies [13,14] but not others [15,16]. Moreover, we could not find an association between smoking and reduction of headache days.…”
Section: Discussioncontrasting
confidence: 82%
“…These results are in line with our data in showing no significant difference in BMI groups and reduction of headache days with categorization of BMI into only two subgroups (< 25 vs. ≥ 25) and a longer follow-up (twelve months). High BMI was a risk factor for increasing headache frequency in some studies [13,14] but not others [15,16]. Moreover, we could not find an association between smoking and reduction of headache days.…”
Section: Discussioncontrasting
confidence: 82%
“…Keith et al [31] found that obese women had increased risk of headache, but not specifically migraine. Téllez-Zenteno et al [32] found that there was no association between the disability and severity of migraine and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the study of Keith et al [17], migraine prevalence was not related to obesity but obese women (BMI of 30) had increased risk for headache (but not specifically migraine) as compared with those with BMI. Téllez-Zenteno et al [26] found that there was no association between the disability and severity of migraine and BMI, as well as no correlation between BMI and the frequency and prevalence of migraine was found in the study of Bigal et al [18] in which 176 subjects (79.5% women, mean of 44.4 years) with normal weight (≤ 24.9), overweight (25–29.9), or obesity (≥30) were observed before and after headache preventive treatment. After treatment, frequency declined in the entire population, but no significant differences were found by BMI group.…”
Section: Epidemiological Relationship Between Headache/migraine Anmentioning
confidence: 99%